Envolvimento do usuário na elicitação de requisitos em projetos ágeis de desenvolvimento de softwares empresariais sob demanda - Porto, Ana Paula da Silva (2021)
Although the literature shows a growing interest in the use of agile methodologies as a strategy to minimize problems in relation to unmet customer expectations, little is still known about how requirements engineering contributes to this purpose. In this sense, the goal of this research is to understand how the involvement of the end user in the agile management of on-demand enterprise software development occurs in order to meet customer expectations. To do so, it looks at the activity of requirements elicitation, which is related to the planned effort in search of the real needs and desires for a project, being more proactive than the simple collection of information. Through systematic reviews of the literature, this study analyzed 25 relevant studies whose synthesis of the data indicated that the theorists of these areas propose definitions for product vision and methods to conceive it, however, the definitions are partial and have limitations such as, for example, high level of abstraction that makes it difficult to operationalize the concept. The methods found are not able to systematize the user's involvement in the process. In order to align the practice and the research objective, a case study was conducted that followed a project of a software development company and its respective customer, carefully observing the agile requirements elicitation phase and its relationship with the acceptance of the product by the users. After consolidating the information, the study reinforced that the success in eliciting requirements from the interaction with software users can be achieved if the communication process is carried out with a minimum of noise. The study also resulted in the need to elicit the requirements from the user's point of view, translating them into a language close to the developers, avoiding difficulties in compression. It became evident that the active participation of the customer, overriding the user, creates barriers to the requirements elicitation phase. A relevant finding is related to the use of hybrid practices in the case, even when the company believes to use, purely, the agile approach. Another relevant insight of this study is the critical role of the Product Owner being an external figure to the development team, impacting the development team's clear understanding of what features are needed in the product.